ANALISIS PERILAKU TOKOH DALAM NOVEL KELUARGA GERILJA KARYA PRAMOEDYA ANANTA TOER: ANALISIS PSIKOLOGI SASTRA - Hugo Foren Dayih; Martono Martono; Agus Wartiningsih (Universitas Tanjungpura, 2021)
AbstractThis study describes the behavior of the characters in the novel Keluarga Gerilja using the operant reinforcement theory of B.F.Skinner. This study uses a descriptive method of qualitative form, and uses a literary psychology approach. The data source of this research is the novel Keluarga Gerilja by Pramoedya Ananta Toer. The data in this study are in the form of quotes, phrases, and sentences that lead to the object of analysis. The data collection technique used is a documentary study. The results showed that the data obtained amounted to 50 data. Implementation plan for learning Indonesian in class XII high school level/equivalent in the 2013 curriculum with basic competencies 3.3 Identifying information, which includes orientation, a series of interrelated events, complications and resolutions, in oral or written history stories, and basic competence 4.3 Constructing the values of historical story information in an explanatory text. Indicator 3.3.1 Collecting important information in historical novels, 3.3.2 Determining the text structure of historical novels, 3.3.3 Comparing historical novels with historical texts. 4.3.1 Rewriting values in historical novels, 4.3.2 Presenting historical novel values into an explanatory text. 4.3.3 Presenting, responding to, revising the prepared explanatory text.Keyword: personality, novel, operant reinforcement theory